A Novel MAX Gene Mutation Variant in a Patient With Multiple and “Composite” Neuroendocrine–Neuroblastic Tumors - Pozza, Carlotta; Sesti, Franz; Di Dato, Carla; Sbardella, Emilia; Pofi, Riccardo; Schiavi, Francesca; Bonifacio, Vincenzo; Isidori, Andrea M.; Faggiano, Antongiulio; Lenzi, Andrea; Giannetta, Elisa (Frontiers in Endocrinology, 2020)
Introduction. Pheochromocytomas (PCCs), paragangliomas (PGLs), ganglioneuroblastomas (GNBs) and ganglioneuromas (GNs) are neuroendocrine neoplasms (NENs) sharing a common embryologic origin from neural crest cells. However, they rarely occur concurrently and recurrently. We describe the case of a 40-year-old woman with “composite PCC-GN” and multiple NENs and neuroblastic tumors. Case presentation. The patient was first referred to our department at the age of 15 years for paroxysmal hypertension, headache, sweating and watery diarrhea. Her personal history included the diagnosis of a pelvic GNB with lumbar-aortic lymph node metastases at 11 months. Her family history was positive for cerebral glioblastoma multiforme (father). An abdominal ultrasound showed a right adrenal mass that histologically was a “composite adrenal PCC-GN”. The symptoms disappeared after surgery. At the age of 20 years the symptoms returned: computed tomography (CT) and 131I-metaiodobenzylguanidine (MIBG) scintigraphy showed an inter-aortocaval mass, found histologically to be an inter-aortocaval PGL. Her symptoms reappeared again at 28 years: CT and magnetic resonance imaging revealed four left adrenal gland nodules, found histologically to be multifocal PCCs with some atypia. Genetic screening for VHL, RET, NF1, Tp53, SDHD, SDHB, SDHC, SDHAF2, SDHAF3, SDHA and TMEM127 was negative. Mutational analysis of the MAX gene revealed the presence of a novel heterozygous variant, c299G>C (p.Arg100Pro, NM_002382.5 that the bioinformatics prediction programs defined as noxious and causative of pathology. Conclusion. This report represents the first description of a cooccurrence of multiple composite PCC-GN and neuroblastic tumors. The long timeline of the presentation of the NENs/neuroblastic tumors from infancy to adulthood requires a lifelong follow-up for this patient. Moreover, the importance of this case lies in the presence of a novel MAX gene variant deleterious, harmful and causative of pathology, confirmed by Sanger sequencing and never been associated before with multiple composite PCC-GN. The present case underlines the importance of precision medicine and molecular diagnoses for hereditary pheochromocytomas and paragangliomas, suggesting that when they occur in early childhood it is necessary to perform an extensive genetic investigation and a lifelong follow-up.